Incorporating Mental Health Into Lifestyle Medicine. Issue 5 (September 2022) - Abascal, Liana; Vela, Alyssa; Sugden, Steve; Kohlenberg, Samuel; Hirschberg, April; Young, Allison; Lane, Karen; Merlo, Gia
The evidence-based interconnection between mental health with lifestyle medicine practice is discussed. The extent to which physical health, and mental and behavioral health overlap are significant, and their interaction is seen in many ways. These bidirectional influences form a continuous thread through all lifestyle medicine pillars. The intersection of mental health and lifestyle should be considered and applied to provide optimal evidence-based lifestyle medicine for all patient populations who will benefit from the specific attention to diet, physical activity, relationships, stress, sleep, and substance use. Lifestyle medicine can be utilized to directly address and treat a range of mental health symptoms and disorders, and physical illnesses. In addition, behavior change skills and addressing the psychological factors contributing to barriers are crucial to helping patients reach their lifestyle medicine goals. Approaches to practice that attend to, and address, mental and behavioral health are relevant to and necessary for all types of providers who work within the lifestyle medicine framework.